PENERAPAN E-GOVERNMENT PADA PELAYANAN PUBLIK DI BIDANG KEPENDUDUKAN KOTA PEKANBARU PROVINSI RIAU - Ahmad Fitra Yuza; Fifi Tri Yuli Astuti; Panca Setyo Prihatin (LPPM Universitas Abdurrab, 2025)
One of the applications of E-Government carried out by the Pekanbaru City government in the population sector is the provision of population administration services using the Waiting Service (LAGU) application which can make it easier for people to obtain population documents that can be processed directly and can be waited. The purpose of this study is to find out the application of E-Government in public services in the population sector of Pekanbaru City and the inhibiting factors in the application of E-Government in public services in the population sector of Pekanbaru City. The research method in this study is descriptive research. Data collection in this research was carried out through observation, interviews and documentation, and data analysis was carried out which included data collection, data reduction, data presentation and drawing conclusions. The results of the research on the implementation of E-Government through the Waiting Service (LAGU) application by applying it at four levels consisting of the preparation level, the maturity level, the stabilization level and the utilization level, so that the implementation of E-Government through the Waiting Service (LAGU) can make it easier for the community to take care of lost, damaged and urgent KTP-El.